Risk Factors Affecting The Incident of Malaria in The Working Area of The Malaimsimsa Public Health Center Sorong City - Yunus, Elga; Haryatmi, Dwi (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Malaria is an infectious disease caused by Plasmodium sp, a single-celled living creature that belongs to the group of the genus Protozoa which is parasitic. The purpose of this study was to determine the influence of environmental factors and behavioral factors on the incidence of malaria in the working area of the Malaimsimsa Community Health Center, Sorong City.Methods: This research is an observational study using a case-control study . The case group in this study included people with malaria as indicated by positive malaria blood test results. Examination of malaria is carried out by means of microscopic examination by making thick and thin blood preparations, stained using Giemsa stain, then identified using a microscope. The control group includes people who are not sick with negative blood test results.Result: The results of this study indicate that all malaria infections that occur are caused by infection with the type of Plasmodium vivax. The risk factors that influence the incidence of malaria are behavioral factors, namely the use of body armor and the use of insect repellent. While the risk factors that do not affect the incidence of malaria are the presence of puddles, temperature and use of mosquito nets.Conclusion : From the results of this study it can be concluded that the factors of stagnant water, temperature and use of mosquito nets are not related to the incidence of malaria, on the contrary the use of body armor and the use of insect repellent have a relationship with the incidence of malaria.